Osnove mikroelektronike: Zbirka vaj z rešitvami - Dogša, Tomaž (2019)
Introduction to Microelectronics: Collection of Solved Problems. This collection of solved problems in microelectronics is designed for students who are experiencing integrated circuit design for the first time. Understanding the problems and solutions requires prior knowledge of microelectronics theory and adequate knowledge of electronics and circuit simulations. Almost all problems have the same structure: text starts at the beginning, followed by analysis or design, and finally, verification with the SPICE simulator. The problems are divided into four groups: MOS transistor, layout design, digital and analogue circuits. For students, the hardest part will probably be designing analogue integrated circuits. The appendix provides an example of a simple project that contains circuit and layout design.
Keywords: microelectronics; electronic circuits; circuit simulation; layout design; SPICE